2018
DOI: 10.12938/bmfh.18-001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Bifidobacterium breve</i> B-3 on body fat reductions in pre-obese adults: a randomized, double-blind, placebo-controlled trial

Abstract: Accumulating evidence suggests a relationship between the gut microbiota and the development of obesity, indicating the potential of probiotics as a therapeutic approach. Bifidobacterium breve B-3 has been shown to exert anti-obesity effects in high-fat diet-induced obese mice. In the present study, the anti-obesity effects of the consumption of B. breve B-3 by healthy pre-obese (25 ≤ BMI < 30) adults were investigated in a randomized, double-blind, placebo-controlled trial (trial registration: UMIN-CTR No. 00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 42 publications
5
75
2
9
Order By: Relevance
“…Bifidobacterium breve B-3 (B-3), a probiotic strain originating from the gut of an infant, has been demonstrated to exert anti-obesity effects [1,2] through mechanisms speculated to include improvement of intestinal barrier function; adiponectin and colonic proglucagon production; and the production of B-3-derived metabolites with anti-obesity activity (e.g., acetic acids and conjugated linoleic acids) [1,3]. In a clinical study on mild obesity subjects, body fat mass was significantly lower in the B-3 group than in the placebo group.…”
Section: Introductionmentioning
confidence: 99%
“…Bifidobacterium breve B-3 (B-3), a probiotic strain originating from the gut of an infant, has been demonstrated to exert anti-obesity effects [1,2] through mechanisms speculated to include improvement of intestinal barrier function; adiponectin and colonic proglucagon production; and the production of B-3-derived metabolites with anti-obesity activity (e.g., acetic acids and conjugated linoleic acids) [1,3]. In a clinical study on mild obesity subjects, body fat mass was significantly lower in the B-3 group than in the placebo group.…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of B. breve B-3 capsules (2 × 10 10 CFU/day) for 12 weeks slightly reduced the TG and improved the HDL-C content in pre-obese subjects, but the changes are not significant when compared to baseline values. However, the probiotic supplementation reduced the body fat in healthy pre-obese subjects; and the lipid profile was not improved significantly [40]. Similarly, L. gasseri BNR17 supplementation (10 9 or 10 10 CFU/day) for 12 weeks reduced the visceral fat mass in obese subjects, but the changes in the TC, LDL-C, HDL-C, and TG were not significant when compared to the placebo control [41].…”
Section: Other Subjectsmentioning
confidence: 87%
“…Studies reported based on the intervention of single-strain probiotic (E. faecium M-74 along with selenium [27]; Saccharomyces cerevisiae var. boulardii CNCM I-1079 [29]; L. rhamnosus GG [30]; Soy milk containing L. plantarum A7 [35]) preparation showed significant hypocholesterolemic effect when compared to the study reported with the intervention of single-strain probiotics (B. breve B-3 [40]; Lactobacillus gasseri BNR17 [41]) preparation; whereas intervention of single-strain probiotics (L. acidophilus [53]; B. animalis subsp. lactis BB-12 [54]) preparation exhibited no beneficial effect on the lipid profile of the studied subjects.…”
Section: Opinion On the Hypocholesterolemic Effect Of Reviewed Probiomentioning
confidence: 99%
See 1 more Smart Citation
“…В группе пациентов с СД2, получающих Lactobacillus в течение 4 нед, сохранялась или нормализовалась чувствительность к инсулину, в то время как в группе плацебо она снижалась. При применении у пациентов с ожирением также было выявлено значительное снижение массы тела, улучшение показателей липидного спектра по сравнению с группой плацебо [61,62].…”
Section: перспективы использования преи пробиотиков трансплантации фunclassified